Dukungan Keluarga dengan Kualitas Hidup pada Pasien Diabetes Melitus Tipe II - Karolina Koryesin; Sri Handayani (Jurnal Indonesia Sehat, 2022)
Backround: According to WHO (world health organization) diabetes mellitus (DM) is a chronic metabolic disease characterized by an increase in blood glucose (or blood sugar) levels causing serious damage to the heart, blood vessels, eyes, kidneys and nerves. Diabetes mellitus type two, usually in adults, occurs when the body becomes resistant to insulin or does not produce enough insulin (WHO, 2019). This study aims to find out the relationship between family support and the quality of life of people with type 2 diabetes. Method: This type of research is literature review, the study population is all journals that have the same title with the title taken by the researcher. The sample is eight journals that have the same title and have the same title. inclusion and exclusion criteria defined by the investigator. Based on data analysis from the eight journals that have been discussed, it can be concluded that family support is very important to be given to family members, especially those who are sick / diabetes mellitus. Conclusion: From the results of the analysis of eight journals, it was found that there was a relationship between family support and quality of life for type II diabetes mellitus patients.